AKIBAT HUKUM PERCERAIAN QOBLA AL DUKHUL OLEH PASANGAN YANG MENIKAH KARENA KAWIN HAMIL - , AULIA NOVERA INDAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowadays, divorce has become a common thing, even for some people it is regarded as a normal thing and become a lifestyle in married life. Currently, the reality there are many couples who get married in early age or often referred to as \"early marriage\". Not a few who perform the marriage because marriage pregnant or become pregnant outside of marriage. In fact, from the psychological side, young couples are not well prepared mentally to build and maintain a household in a marriage bond. Consequently, shortly after the wedding is often followed by a divorce, one of which is divorce Qobla al Dukhul. The purpose of the Job Training , is to develop or implement a theory that has been gained during the lecture to the real work and practice to get the data both primary and secondary of the legal consequences of divorce Qobla al Dukhul of married couples as married pregnant. Based on the results of research, divorce Qobla al Dukhul is a divorce which performed after the marriage ceremony process where the wife is divorced her husband before the intercourse as husband and wife. In this case, there are four legal consequences which will be discussed by the author. They are the consequences toward the wife of the the waiting period, toward the husband, as a result of the status of children born to married couples because marriage is pregnant and toward the property.